Polarization and Emotional Response to Threats: The Case of Covid-19 - Hemsley, Pedro; Moraes, Flavio; Pavão, Lynda (Advances in Social Sciences Research Journal, 2024)
In this paper, we ask how polarization is related to innate responses to threats. Through an online survey, we study the relationship between polarization about Covid-19 mitigation measures and psychopathy, a condition characterized by a reduced emotional response to perceived threats. We find that polarization is significantly lower for individuals with high psychopathy traits. This suggests that polarization over emotionally-charged political issues may be related to a biological mechanism that operates in high-risk environments: the fight or flight response.